Porcine Endogenous Retrovirus Infects but Does Not Replicate in Nonhuman Primate Primary Cells and Cell Lines - Ritzhaupt, Armin (American Society for Microbiology, 2002)
Porcine endogenous retroviruses (PERV) can infect human cell lines in vitro; hence, there is a presumed risk of viral exposure to a recipient when pig cells are transplanted into humans (xenotransplantation). Nonhuman primates (NHP) are considered a potential permissive animal model to study the risk of in vivo infection of PERV after xenotransplantation. We set out to determine whether PERV can infect and replicate in NHP primary cells or established cell lines from African green monkey, rhesus macaque, and baboon. We confirm that the NHP cell lines under investigation were infected with PERV as measured by detection of viral DNA and RNA by PCR and reverse transcription (RT)-PCR, respectively, indicating that a functional receptor must be present on the cell surface. However, the load of detectable viral DNA in infected NHP cells declined over time, and the cells never had detectable reverse transcriptase activity. Utilizing quantitative real-time TaqMan PCR we found detectable levels of unintegrated DNA intermediates, but the levels were approximately 100-fold lower compared to HEK 293 cells infected with PERV. Virions released from infected NHP cells could productively infect naïve human cell lines, HEK 293 and HeLa, as shown by RT-PCR and RT assay. However, naïve NHP cells remained negative in RT-PCR and RT assay after exposure to virions from infected NHP cells. Together our data demonstrate that NHP cells are not permissive to productive replication by PERV, presumably due to inefficient cell entry and replication. In light of these observations, the appropriateness of NHP as suitable animal models to study PERV infection in vivo needs to be reevaluated.